Spatiotemporal variation of the water and sediment dynamics of the middle Yellow River Basin, China - Zhang, Xiang; She, Dongli; Ge, Jiamin; Cao, Taohong; Xia, Yongqiu (Hydrological processes, 2022)
After decades of comprehensive management, the hydrology and sediment dynamics of the middle Yellow River Basin have changed significantly. However, the comprehensive evaluation of the water and sediment regimes and its potential attribution at the regional scale are limited. In this study, the hydrological characteristics and in‐reach sediment budget in the Coarse Sandy Hilly Catchments (CSHC) region and their potential attribution were investigated by using data from hydrological stations in the mainstream and tributaries and data from soil and water conservation measures (SWCMs) in different river reaches. The results indicated that the runoff and sediment load of the mainstream showed obvious spatial heterogeneity, both of which revealed a very significant decreasing trend from 1956 to 2018 (P < 0.01). The spatial heterogeneity of sediment load along the mainstream was more obvious than that of streamflow, and the Toudaoguai and Fugu stations had the largest difference in sediment transport trends. During the P1 period (1956‑1968), the streamflow of each reach was sufficient, and the riverbeds of the mainstream and channel on both banks were subject to serious scouring. In the P2‑P3 period (1969‑2018), in‐reach water decreased continuously, and the mainstream began to show a process from slight scouring to no scouring and even sediment deposition. Except for climate change being the main factor in streamflow reduction during the P2 period (1969‑1999) at the Fugu and Wubao stations, anthropogenic activities were the primary factors leading to the reduction in streamflow and sediment load in the CSHC region. Under the influence of the same measures, the sediment reduction rate in this region was greater than the runoff reduction rate. Furthermore, the SWCMs in different reaches indicated great diversity in the benefits of water and sediment reduction. Therefore, zoning regulation of the CSHC region should be carried out in the future, and the sustainable development of the regional vegetation ecosystem should be maintained. The runoff and sediment load of the mainstream showed obvious spatial heterogeneity and revealed a very significant decreasing trend in 1956–2018. Reservoir construction caused the sudden change of sediment load in the mainstream. The sediment reduction rate caused by the same measures was greater than the runoff reduction rate.